PERANCANGAN APLIKASI REKAM DATA CUACA HASIL PENGAMATAN OBSERVER STASIUN METEOROLOGI BMKG BERBASIS WEBSITE (Studi Kasus : Stasiun Meteorologi Supadio Pontianak) - Agung Sasongko (Universitas Bina Sarana Informatika, 2014)
AbstractBadan Meteorologi Klimatologi dan Geofisika (BMKG) is one of the Indonesian government-owned entity that specifically address the issue of climate and weather in Indonesia. Information of weather data are needed both by government and the public, it relates to the planning of work activities that depend on weather conditions, such as agriculture, shipping, fishing, flight, and so forth. Observer is the officer who specifically collect information each time weather conditions. The data from the observer is then further processed to become the weather information and forecast weather. Often the work of the observer becomes longer because besides entry the data, the observer must also do codefication and recreate reports from the data ME-48. This writing discusses the development of applications to assist observers in processing weather data record using SDLC development methods as well as qualitative descriptive research method. Results of application development shows that the application can process the data ME-48 into a form reports like ME-45, WXREV, Rain Card, Climatology and average monthly weather elements that usually must be done manually by the observer, is now using the application does not require long time to generate all the reports.Keywords: Observer, Website, Weather Application.